An Overview Of Mechanism Of Nasya Karma - Nibe , C S (International Research Journal of Ayurveda & Yoga, 2021)
Speed and accuracy are the prime demands of the modern era. To cope with this situation everybody has to face a hectic, competitive, and stressful life. People cannot pay attention to their physical and mental health. Irregular food habits, suppression of natural urges, lack of proper sleep, and less time for relaxation being part of our life enhances the incidence of mainly having a psychosomatic origin. The nose is a sense organ that performs two functions i.e., olfactory and respiratory. Due to its direct contact with the external environment, it is exposed to a lot of microorganisms and pollutants present in the atmosphere. Due to environmental pollution and busy life rhinitis is a common disease in this present. So that ’Nasya’ (Nasal therapy) being prime therapy for maintaining the health of Urdhva Jatrugata rogas (Disease of head and neck) and specially Nasagata rogas (diseases of the nose).